Theocracy : reflections of the relationship between God and King in Samuel-Kings and Chronicles - Cezula, Ntozakhe Simon (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MDiv (Old and New Testament))--University of Stellenbosch, 2006.